Comparison of experimental and Computational Fluid Dynamics (CFD) studies of slug flow in a vertical riser - Abdulkadir, M.; Hernandez-Perez, V.; Lo, S.; Lowndes, Ian; Azzopardi, Barry J. (Elsevier, 2015)
This paper presents a comparison of the results obtained from experiments and CFD studies of slug flow in a vertical riser. A series of two experimental investigations were carried out on a 6 m vertical pipe with a 0.067 m internal diameter charged with an air–silicone oil mixture. For the first set of experiments, the riser was initially full of air, and then liquid and gas flows set to liquid and gas superficial velocities = 0.05 and 0.344 m/s, respectively, electrical capacitance tomography (ECT) and wire mesh sensor (WMS) transducers were employed. In the second one, the riser was initially full of (static) liquid, and then liquid and gas flows set to liquid and gas superficial velocities = 0.05 and 0.344 m/s, respectively, only ECT was used. A characterisation of the observed slug flow regimes was carried out. This includes the evaluation of the instantaneous distribution of the phases over the pipe cross-section, the Probability Density Function (PDF) of void fraction, time series of cross-sectional void fraction, Power Spectral Density (PSD), structure velocity of the Taylor bubble, lengths of the liquid slug and Taylor bubble and void fractions in the liquid slug and Taylor bubble. The simulation results were validated both qualitatively and quantitatively against experimental data. A reasonably good agreement was observed between the results of the experiment and CFD.